UV/vis spectrophotometric determination of slow equilibrated N(1)-H missing deprotonation constant of a pyrimidine and thiopyrimidine: The final situation of the four pK(a) values - KILIÇ, HASAN (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
The missing acidity constant of recently synthesized 5-benzoyl-1-(methylphenylmethyleneamino)-4-phenyl-1H-pyrimidine-2-one (I) and 5-benzoyl-1-(methylphenylmethyleneamino)-4-phenyl-1H-pyrimidine-2-thione (II) are investigated as a function of time at pH values from 1.0 to 3.20 for I and from 1.0 to 4.06 for II using UV/vis spectroscopic analysis of their aged solutions, at a temperature of 25 +/- 0.1 degrees C. In this study, a novel time-dependent isosbestic point method was developed to confirm the presence of any weak acid - base equilibrium and the detection of related equilibration time. The missing acidity constants for each of I and II were determined in 5.0% v/v aqueous methanol. Plausible acid base equilibrium mechanism for the missing acidity constant was presented for each of the compounds based on the extensive experimental UV/vis data. In this context, all the acid base equilibria for each of the regarding compounds were completely revised through different pH values. (c) 2019 Published by Elsevier B.V.
Keywords: Acidity constants; Pyrimidines; Thiopyrimidines; Semicarbazones; Thiosemicarbazones; Uv/vis spectroscopy; ACID-BASE EQUILIBRIA; ELECTRONIC ABSORPTION; OXALYL COMPOUNDS; DERIVATIVES; ENOLIZATION; BEHAVIOR